CYP1B1 G199T Polymorphism Affects Prognosis of NSCLC Patients with the Potential to Be an Indicator and Target for Precise Drug Intervention. (9th March 2017) - Li, Fengzhou; Zhang, Shaofeng; Zhang, Qi; Li, Jinxiu; Zhao, Shilei; Gu, Chundong
Abstract : CYP1B1 gene single nucleotide polymorphisms G119T, C432G, and A453G were tested among 164 NSCLC patients treated by Video-Assisted Thoracoscopic Surgery. After a follow-up period of 5 years, it was found that CYP1B1 G119T mutant genotypes were related to a higher risk of tumor recurrence and death after surgical resection. However, C432G and A453G genotypes had no influence on long-term prognosis of the study cohort. Thus, G199T alleles are supposed to be an auxiliary predictor for prognosis of NSCLC patients and a potential target for precise drug intervention, as well as a candidate for further anticancer drug research.